Molecular insight into the regulation and function of MCAK. (3rd July 2016) - Ritter, Andreas; Kreis, Nina-Naomi; Louwen, Frank; Wordeman, Linda; Yuan, Juping
Abstract: Chromosome stability is ensured by precisely fine-tuned dynamics of mitotic spindles, which are controlled by a network of various microtubule-associated and interacting proteins including the kinesin-13 family. The best characterized member of this family is the mitotic centromere-associated kinesin (MCAK). By efficiently depolymerizing microtubules, MCAK influences various key events during mitosis. MCAK itself is regulated by its interaction partners, its intrinsic conformation switch and the phosphorylation of mitotic kinases like Aurora A/B, cyclin-dependent kinase 1 and Polo-like kinase 1. Perturbing its regulation alters MCAK's conformation, catalytic activity, subcellular localization and stability, leading further to mitotic defects in spindle formation and chromosome movement. Indeed, MCAK is aberrantly regulated in various cancer types, which is linked to increased invasiveness, metastasis and drug resistance. In the current review, we summarize recently published data concerning MCAK, correlate its conformation changes with its depolymerization activity and function, propose a model of its regulation by multiple mitotic kinases and highlight its potential involvement in oncogenesis and drug resistance.